Occurrence of Enneothrips flavens moulton and Stegasta bosquella (chambers) and its effects on agronomic traits of wild Arachis accessions - Michelotto, Marcos Doniseti; de Godoy, Ignácio José; Fávero, Alessandra Pereira; Carrega, Willians Cesar [UNESP]; Finoto, Everton Luiz (My University, 2013)
Some wild species of the genus Arachis have demonstrated potential for improvement of peanuts. This work was performed to evaluate the occurrence and symptoms of Enneothrips flavens and Stegasta bosquella and its effects on agronomic traits of wild Arachis accessions. Nine accessions of wild Arachis species and a commercial A. hypogaea variety were studied in a split plot statistical scheme with a completely randomized block design and four replications. The main plots consisted of plants sprayed or not sprayed for insect control, while the subplots comprised the peanut accessions. Accessions GKP10017 (A. cardenasii) and V7639 (A. kuhlmannii) showed the lowest percentages of leaflets with E. flavens and S. bosquella. Accessions V9912, V7639 and V8979 (all three A. kuhlmannii) and V13250 (A. kempff-mercadoi) showed the lowest responses to insecticide application among the various plant traits evaluated. These accessions are of interest for further studies to identify mechanisms of resistance, to be used in breeding programs for resistance to these insects.
Ocorrência de Enneothrips flavens moulton e Stegasta bosquella (chambers) e seus efeitos em caracteres agronômicos de acessos de espécies silvestres de Arachis
Keywords: Insect pests; Plant resistance; Rednecked peanutworm; Thrips; Wild peanut